Evidence-based teaching in the 21st Century: The missing link - Hunter, William J. (Canadian Journal of Education/Revue canadienne de l'éducation, 2017)
Throughout my career, I have struggled with the fact that teacher preparation programs do not include a course in educational research. When I mention this to colleagues (or students), a highly predictable response is “Why should teacher candidates learn about research?” After years of trying to give a calm and rational response to that question, I have recently begun to answer with some questions of my own: • Why should medical students learn about medical research? • Why should nursing students learn about health science research? • Why should law students learn about legal research? • Why should engineering students learn about engineering research?